Analysis of Training Needs for Making Teaching Materials Based on Information Technology for Elementary School Teachers in Padang Pariaman Regency - Abna Hidayati; Alwen Bentri; Vevi Sunarti (Universitas Negeri Padang, 2019)
The training in developing information and communication technology-based teaching materials for elementary school teachers in Padang Pariaman Regency is based on an analysis of the needs of teachers regarding the development of information and communication technology-based teaching materials and the level of teacher mastery over the development of teaching materials. The purpose of this study was to determine the analysis of training needs for the development of information technology-based teaching materials. This type of research is quantitative using a questionnaire. The method used in this research is quantitative. The population in this study were 350 classroom teachers in Padang Pariaman Regency. Samples were taken as many as 30 people randomly. The research instrument was a questionnaire that was processed using a percentage technique. The results showed that the level of importance of the development of teaching materials was classified as high at 66%. Furthermore, 80% of teachers stated that they really need teaching material development materials, 35% really needed to have the ability to select material sources and as many as 28% of teachers really needed the ability to make teaching materials. Based on the results of the study it can be suggested 1) teachers are given the opportunity to develop teaching materials, 2) the school needs to provide training in the development of teaching materials for teachers. must be factual and concise.Keywords: Needs Analysis, Training, Teaching Materials, Based on Information Technology